Colonic Gastrointestinal Stromal Tumor: A Population-Based Analysis of Incidence and Survival - Zhiqiang Liu; Yan Sun; Yongfeng Li; Jingyuan Zhao; Shihong Wu; Zibo Meng; Heshui Wu (Gastroenterology Research and Practice)
Objectives. The incidence of gastrointestinal stromal tumors (GISTs) located in the colon is rare. Current studies mainly focus on case reports for colonic GISTs. Therefore, a population-based analysis was useful to guide the clinical treatment strategy. Methods. The patients were selected from 2000 to 2015 based on Surveillance, Epidemiology, and End Results (SEER) database. Patients’ demographics, tumor characteristics, incidence, treatment, and survival were retrieved for analysis. Results. 249 cases of colonic GISTs were collected. The male-female ratio was close to 1 : 1 (male 51.41%, female 48.59%). Most cases were Caucasians (70.28%), and African Americans accounted for 19.68%. Age of diagnosis ranged from 21 to 93 years with a median (mean) age of 67.5 (65.56). The incidence was rare, only 0.018 per 100,000. It had an annual percentage change (APC=−0.7728) without statistical significance (P=0.5127) while the incidence of other GISTs increased from 2000 to 2015, with an annual percentage change of 3.9% (P=0.0001). Surgery was associated with better prognosis whereas chemotherapy did not impact the survival rate. Conclusion. Colonic GIST is a rare solid tumor, and the incidence is stable. The entity has a poorer prognosis than other GISTs. Surgery improved the survival rate, while chemotherapy did not.